Modifikasi Aspal Konvensional Penetrasi 60/70 Menggunakan Lateks Kebun Dengan Variasi Konsentrasi Dan Kadar Karet Kering Lateks - Rani Yuliantari; Rozanna Sri Irianty; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Natural rubber is an natural polymer that is potentially used as n asphalt additive. This research aims to determine influence of dry rubber content and amount of field latex to asphalt modified properties. In this study, has been used are latex with 22% of dry rubber content (non centrifugated) and 56% of dry rubber content (centrifugated). The sample made by adding field latex in to asphalt at 160ºC with 20 minute of blending time. The concentrations of latex were 5.0%, 7.5%, 10.0%, 12.5% and 15.0% w/w in the mixture. The samples were tests included penetration, softening point, marshall stability, and penetration after loosing weight, with standard of Spesifikasi Umum Binamarga Divisi 6.2010. The result showed that dry rubber content and amount of latex affects the value of test parameters asphalt modified. The best result is obtained from adding 10% w/w non centrifugated latex with penetration, softening point, stability, and penetration after TFOT, respected are 56 dmm, 58ºC, 1554 kg and 55 dmm. The result of this study indicated that addition of non centrifugated latex can improve asphalt properties.Keywords: asphalt modified, asphalt properties, dry rubber content, field lateks, polymer